Chemical Aerosol Flow Synthesis of Semiconductor Nanoparticles - Didenko, Yuri T; Suslick, Kenneth S (Journal of the American Chemical Society, 2005)
Nanometer-sized semiconductor particles (quantum dots) have been the subject of intense research during the past decade owing to their novel electronic, catalytic, and optical properties. Fundamental properties of these nanoparticles (1−20 nm diameter) can be systematically changed simply by controlling the size of the crystals while holding their chemical composition constant. We describe here a new methodology for the continuous production of fluorescent CdS, CdSe, and CdTe nanoparticles using ultrasonically generated aerosols of high boiling point solvents. Each submicron droplet serves as a separate nanoscale chemical reactor, with reactions proceeding as the liquid droplets (which hold both reactants and surface stabilizers) are heated in a gas stream. The method is inexpensive, scalable, and allows for the synthesis of high quality nanocrystals. This chemical aerosol flow synthesis (CAFS) can be extended to the synthesis of nanostructured metals, oxides, and other materials.